Antioxidant activity of soybean and gembus tempeh - Sunarti Sunarti; Rosyida Awalia Safitri; Agustina LN Aminin; Mohammad Sulchan; Banundari Rahmawati (International Journal of Public Health Science (IJPHS), 2021)
Soybean tempeh and gembus tempeh are traditional foods that have long been known in Indonesia, which in a modern way are classified as functional food. Various studies related to the antioxidant activity of soybean and gembus tempeh has been reported. This study aimed to compare the antioxidant capacity of soybean tempeh and gembus tempeh that are circulating in the community. The results of the research are expected to be an evaluation of soybean tempeh and gembus tempeh quality available in the market. The results of this research are expected to be an evaluation of soybean tempeh and gembus tempeh quality available in the market. The research design was a cross-sectional experimental study to measure antioxidants activity of 31 soybeans tempeh and 29 gembus tempeh. Sample of this study was selected through simple random sampling technique. The measurement of antioxidant activity carried out was the 2.2-diphenyl 1-picrylhydrazyl (DPPH) method; ethanol extraction of 95%. Results revealed that the antioxidant activity of gembus tempeh was significantly higher than soybean tempeh; (32.521; 19.831) vs., (17.016; 13.195), respectively.